Relationship between cholesterol levels and smoking behavior among active smokers - Anwari, Farida; Rohma, Martina Kurnia; Charisma, Acivrida Mega; Nurrosyidah, Iif Hanifa; Nurdianto, Arif Rahman; Putra, Galih Satrio; Dimas, Dimas (Gaceta Médica de Caracas, 2022)
Introduction: Smoking behaviour is one of the factors that can cause serious and deadly diseases. Cigarette chemical content can reduce High-Density Lipoprotein (HDL) levels and increase Low-Density Lipoprotein (LDL) levels. It can cause fat metabolism disorders and are at risk for heart disease, cancer, and others. This study aimed to determine the relationship between cholesterol and smoking behaviour among active smokers.